PENGARUH PENGGUNAAN METODE PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN TEKNIK LISTRIK TERHADAP HASIL BELAJAR SISWA KELAS X DI SMK N 1 PADANG - Randi Winanda; Hanesman Hanesman; Almasri Almasri (Universitas Negeri Padang, 2015)
This research is aimed to know the difference between Contextual Teaching and Learning model and Cooperative model in learning ouput in Teknik Listrik for grade X Electronic Engineering of SMKN 1 Padang on entire semester, academic year 2014/2015. This type of research is quasi experimental. Participant were slected by non-probability sampling technique with purposive sampling. 30 students from Class X AVB, which served as a controling class, used Cooperative model. 30 students from Class X AVA, which served as experimental class, used student cooperative type Contextual Teaching and Learning model. Data is collected from the final test then was analyzed for homogeneity testing, normality and hypothesis testing. The result indicates that experimental class has mean 79,6, while controlling class has mean 77,4. The result of hypothessis testing on significant level α=0,05 is 2,01 > 1,70 and the percentage effect 2.84 %. Since the tcount is higher than the t table, then Ho is rejected and Ha is accepted. It can be inferred that Contextual Teaching and Learning model is better than Cooperative model. Keywords: Contextual Teaching and Learning model, Cooperative model, Learning outcomes